PCR-based Diagnosis of Mucormycosis Targeting Mucorales-specific Genes. (4th October 2017) - Baldin, Clara; Soliman, Sameh; Jeon, Heewon; Gebremariam, Teclegiorgis; Alkhazraji, Sondus; Bruno, Vincent; Edwards, John; Ibrahim, Ashraf
Abstract: Background: Mucormycosis is a life-threatening infection caused by fungi in the order Mucorales. Among them, Rhizopus spp . are responsible for 50-70% of all cases of mucormycosis, followed by Mucor spp . and Lichtheimia spp . Standard treatment of mucormycosis involves surgical removal of infected tissue and antifungal therapy. However, the rapid progression of the disease and the current lack of early and reliable diagnostic assay contribute to the high mortality rates of 50%–100%. Methods: We propose a PCR-based approach targeting the spore coating protein homolog encoding CotH genes. CotH are universally and uniquely present among Mucorales and they encode cell surface proteins that are required for mucormycosis pathogenesis. Bioinformatic analyses were used to identify short consensus sequences present in CotH genes from different Mucorales to be used as PCR primers. Candidates were tested for the amplification of PCR-products from gDNA of different Mucorales. The sensitivity of selected primers was tested using biological samples spiked with different spores concentrations. Finally, the best candidate primers were used to detect the presence of pathogen DNA from biological samples taken from mice infected intratracheally with different Mucorales. Results: Our best candidate primers could amplify the specific sequence from R. delemar, R. oryzae, M. circinelloides, L. corymbifera and Cunninghamella bertholletiae . These primers had a sensitivity of detecting 10 spores into a spiked sample. The specificity for the unique CotH target enabled us to differentiate between Mucorales and closely related filamentous fungus, e.g., Aspergillus fumigatus . Genomic DNA extraction was successful from all considered biological samples; remarkably, infection was successfully detected from biological samples taken from mice infected with different Mucorales as early as 24 hours post infection. Conclusion: We have successfully developed a simple PCR-based approach which is fast, reliable and sensitive enough to detect Mucorales gDNA in murine biological samples as early as 1 day post infection. CotH genes as target will allow a better differentiation between Mucorales species and other closely related filamentous fungi. Disclosures: All authors: No reported disclosures.